PROGRAM APPLICATION PAGE WEB BROWSER TO DISPLAY USING THE INTERNET IN DELPHI 5 - Yudianto Sujana; Sahni Damerianta Purba. Skom. MM (Jurnal Sistem Informasi, 2002)
The Internet is an unlimited source of information, information on the Internet arepresented in various forms. One form of information available on the Internet is theWorld Wide Web (WWW). WWW is a form of multimedia information preparedusing language that is Hypertaxt Markup Language (HTML).To access the WWW needed a web browser. Web Browser works as a client Dimanclient requested a file from a server in the form of HTML and also displaysinformation to the desktop in the form of multimedia.To create a Web Browser needed an object-oriented programming language calledObject Oriented Program (OOP). One of these programming languages are Delphi 5.With Delphi 5 is very possible someone can make a web browser, since Delphi 5support in the Internet-based programming.